2023
DOI: 10.3390/brainsci13071068
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Quality of Sleep and Social Participation of Stroke Patients

Abstract: (1) Background: Stroke patients are exposed to various psychosocial factors, such as depression, anxiety, and stress, which can cause problems with respect to their quality of sleep and social participation. (2) Objectives: We analyzed the causal relationships between the factors affecting sleep quality and social participation in hospitalized and community-based stroke patients using a path analysis model. (3) Methods: A questionnaire survey was administered to stroke patients from June to November 2020 using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
1
Order By: Relevance
“…However, it is interesting to note that a study on stroke patients also affirmed the correlation between sleep quality, stress, depression, and social participation. Yet, the path analysis in that article indicated that depression serves as a risk factor for sleep quality, presenting a different conclusion from our study (45). This suggests the presence of a complex, potentially bidirectional interaction between sleep quality and stress.…”
Section: Discussioncontrasting
confidence: 94%
“…However, it is interesting to note that a study on stroke patients also affirmed the correlation between sleep quality, stress, depression, and social participation. Yet, the path analysis in that article indicated that depression serves as a risk factor for sleep quality, presenting a different conclusion from our study (45). This suggests the presence of a complex, potentially bidirectional interaction between sleep quality and stress.…”
Section: Discussioncontrasting
confidence: 94%